2018
DOI: 10.2147/ijwh.s142052
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in dispensed analgesics in Sweden during 2006–2015 – an observational, nationwide, whole-population study

Abstract: IntroductionA potentially illuminating way of looking at gender differences in health and disease is to study differences in drug utilization. The aim of this study was to describe gender differences in dispensed analgesics (including nonsteroidal anti-inflammatory drugs [NSAIDs]) in Sweden during 2006–2015.Materials and MethodsThe Swedish Board of Health and Welfare holds an open, Anatomical Therapeutic Chemical (ATC)–based statistical database containing aggregated data on all dispensed prescription drugs in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 45 publications
5
11
0
Order By: Relevance
“…Consistent with previous research [29], women in our study reported higher pain levels as measured with VAS than men. We also found that women reported more frequent use of analgesics than men, which is consistent with a previous study reporting that women across ages are prescribed more non-steroidal anti-inflammatory drugs than men [30]. This may reflect different pain coping strategies between sexes [31] or tentatively, that women are more likely to undertake preventive care and thereby, use analgesics as a way to prevent pain.…”
Section: Discussionsupporting
confidence: 90%
“…Consistent with previous research [29], women in our study reported higher pain levels as measured with VAS than men. We also found that women reported more frequent use of analgesics than men, which is consistent with a previous study reporting that women across ages are prescribed more non-steroidal anti-inflammatory drugs than men [30]. This may reflect different pain coping strategies between sexes [31] or tentatively, that women are more likely to undertake preventive care and thereby, use analgesics as a way to prevent pain.…”
Section: Discussionsupporting
confidence: 90%
“…Two thirds of the participants in this study were women, which reflects that there are more women than men among pharmacy customers and that women use OTC drugs more frequently compared with men [3,23,24]. Regarding analgesics, this may be related to menstrual pain and that women seem to suffer from pain at rates higher than men and are more sensitive to pain [25].…”
Section: Discussionmentioning
confidence: 93%
“…The number of female participants enrolled in our study was higher as has been reported by previously conducted studies observing more females using gabapentinoids for neuropathic pain. 20,21 Higher ratio of females could be due to a higher propensity of females for chronic pain due to gender-based biological differences in pain modulation, neural structures, sex hormones and neuroimmune differences. 20 In our study, the most common aetiology was diabetic neuropathy followed by radicular pain which could be due to a higher prevalence of diabetes mellitus (16.98%) in the Pakistani population.…”
Section: Discussionmentioning
confidence: 99%
“…20,21 Higher ratio of females could be due to a higher propensity of females for chronic pain due to gender-based biological differences in pain modulation, neural structures, sex hormones and neuroimmune differences. 20 In our study, the most common aetiology was diabetic neuropathy followed by radicular pain which could be due to a higher prevalence of diabetes mellitus (16.98%) in the Pakistani population. 22 Our results are in agreement with a study carried out in a tertiary care hospital of Saudi Arabia reporting diabetic neuropathy as the most common aetiology; another study reported radiculopathies and post-surgical pain as the most common conditions associated with neuropathic pain.…”
Section: Discussionmentioning
confidence: 99%